BRG1 Activates PR65A Transcription to Regulate NO Bioavailability in Vascular Endothelial Cells - Chen, Baoyu; Zhao, Qianwen; Xu, Tongchang; Yu, Liming; Zhuo, Lili; Yang, Yuyu; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Vascular endothelial cells contribute to the pathogenesis of cardiovascular diseases by producing and disseminating angiocrine factors. Nitric oxide (NO), catalyzed by endothelial NO synthase (eNOS), is one of the prototypical angiocrine factors. eNOS activity is modulated by site-specific phosphorylation. We have previously shown that endothelial-specific knockdown of BRG1 in Apoe-/- mice attenuates the development of atherosclerosis, in which eNOS-dependent NO plays an antagonizing role. Here we report that attenuation of atherogenesis in mice by BRG1 knockdown was accompanied by partial restoration of NO biosynthesis in the arteries and a simultaneous up-regulation of eNOS serine 1177 phosphorylation. In indeed, BRG1 depletion or inhibition ameliorated oxLDL-induced loss of NO bioavailability and eNOS phosphorylation in cultured endothelial cells. Further analysis revealed that BRG1 regulated eNOS phosphorylation and NO synthesis by activating the transcription of protein phosphatase 2A (PP2A) structural subunit a (encoded by PR65A). BRG1 interacted with ETS1, was recruited by ETS1 to the PR65A promoter, and cooperated with ETS1 to activate PR65A transcription. Finally, depletion of ETS1, similar to BRG1, repressed PR65A induction, normalized eNOS phosphorylation, and rescued NO biosynthesis in endothelial cells treated with oxLDL. In conclusion, our data characterize a novel transcriptional cascade that regulates NO bioavailability in vascular endothelial cells.